2016
DOI: 10.1111/exd.12987
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals induced by sunlight in different spectral regions – in vivo versus ex vivo study

Abstract: Sunlight represents an exogenous factor stimulating formation of free radicals which can induce cell damage. To assess the effect of the different spectral solar regions on the development of free radicals in skin, in vivo electron paramagnetic resonance (EPR) investigations with human volunteers and ex vivo studies on excised human and porcine skin were carried out. For all skin probes, the ultraviolet (UV) spectral region stimulates the most intensive radical formation, followed by the visible (VIS) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 43 publications
2
56
0
2
Order By: Relevance
“…In this study, the NIR irradiance dose was 2.1 J/cm 2 and therefore lower than the natural sunlight radiation, which makes a realistic extrapolation to in vivo conditions possible. New results on the comparison between ex vivo and in vivo findings have shown that in vivo many more radicals are formed compared to ex vivo [37]. Therefore, in vivo a protection could be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the NIR irradiance dose was 2.1 J/cm 2 and therefore lower than the natural sunlight radiation, which makes a realistic extrapolation to in vivo conditions possible. New results on the comparison between ex vivo and in vivo findings have shown that in vivo many more radicals are formed compared to ex vivo [37]. Therefore, in vivo a protection could be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Krutmann et al 2017 1 Krutmann et al 2012 5 Bonnet et al 2015 7 Dupont et al 2013 8 Marionnet et al 2015 9 Lohan et al 2016 10 McDaniel et al 2018 18 Solar radiation UV VL IR UV, VL, IR affect the epidermis, dermis, and hypodermis leading to inflammation and oxidative damage. Although all UV wavelengths contribute to photo-aging, UVA1 causes major radiation damage due to its long wavelength.…”
Section: Publication/year Exposome Factor Impactmentioning
confidence: 99%
“…Visible light and infrared light penetrate into the dermis and have been shown to induce inflammation leading to dermal matrix degradation 7,10. Infrared light can cause skin darkening in darker skin types, which was not significant in the lighter skin types 7,10.…”
mentioning
confidence: 99%
“…In contrast to other wavelengths of VIS, HEVIS exposure leads to a significant decrease in viability of different skin cell lines and more pronounced shrinkage of the extracellular matrix (ECM) . Like UVA, HEVIS appears to exert its effects mainly through the generation of ROS, accounting for a substantial part of the amount generated by natural midday sunlight in human skin . Blue light photon ROS production efficacy corresponds to 25% of UVA in human keratinocyte mitochondria .…”
Section: Introductionmentioning
confidence: 99%